KINERJA BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN LUMAJANG - Djoko Soejono; Dimas Bastara Zahrosa; Ariq Dewi Maharani; Yustri Baihaqi; Amam Amam (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
Regulation of the Minister of Villages, Development of Disadvantaged Areas, and Transmigration of the Republic of Indonesia Number 4/2015 states that Village-Owned Enterprises (BUMDes) are business entities whose entire or most of the capital is owned by the village through direct participation from separated village assets to manage assets, services, and other businesses for as much as possible the welfare of the village community. The research aims to assess the performance of BUMDes in Lumajang Regency. The focus of research on BUMDes Arya Wiraraja is on a financial perspective, a customer perspective, internal business process, a growth and learning perspective, and inhibiting and supporting factors for BUMDes development. The research data consisted of primary data and secondary data. The data analysis used descriptive analysis, financial performance analysis, and Force Field Analysis (FFA). The results from the financial perspective fall into the reasonably good category, because the level of acceptance, net income, ROI, ROE, and NPM has fluctuated. The customer perspective is in a good category because customers are satisfied with BUMDes services, but employee productivity is in the good enough categories, because employee performance fluctuates. The supporting factors for BUMDes consist of various business units such as the trade system unit, savings and loan units, service units, livestock farming business units, and tourism units. In contrast, the inhibiting factor for BUMDes is the formation of Standard Operating Procedures (SOP) in each business unit. The conclusion of the study shows that the overall performance of BUMDes is quite good.